The impact and importance of place on health for young people of Pasifika descent in Queensland, Australia: a qualitative study towards developing meaningful health equity indicators - Jo Durham; Nicola Fa'avale; Andrew Fa'avale; Catrina Ziesman; Eden Malama; Sarai Tafa; Tamaika Taito; Jori Etuale; Mitieli Yaranamua; Ueta Utai; Lisa Schubert (BMC, 2019)
Abstract Background Health equity is a priority in the global sustainable development agenda. Available health equity indicators often focus on health outcomes, access to healthcare, risk factors and determinants such as income, education, and gender. Less attention has been given to other social determinants, including those related to place and ethnicity. Measures such as income, education, and gender, however, may not provide policy-makers with sufficient information to redress inequities. In this paper, we begin to develop health equity indicators for young Pasifika peoples in Logan, Queensland, Australia. While health data on Pasifika young people in Queensland is scant, available data suggests significant inequalities. The purpose of the study was to develop an understanding of the drivers of these disparities through the lens of the social determinants of health, to create health equity indicators. Methods Following meetings with community stakeholders to develop respectful and collaborative partnership processes, we took a youth participatory action research approach. Six peer researchers (3 male, 3 female) were recruited from the Logan area for the project. Following training, the peer researchers undertook 31 qualitative interviews with young Pasifika (16-24 years old). Data was manually analysed, coded and grouped into themes to develop the draft indicators. Interviews used the culturally appropriate Talanoa storytelling approach. Results Six key themes were identified from the interviews and were used to develop example indicators related to: spiritual and socio-cultural dimensions, place, access to culturally responsive services, economic and material dimensions and political dimensions. The results demonstrate health inequities experienced by Pasifika populations are strongly linked to place and their economic, social and cultural position. Conclusions This study emphasises the need to understand the multiplicity of place-based factors that interact in complex ways to shape health inequities for young Pasifika peoples. It highlights health equity indicators must go beyond healthcare services, outcomes and a limited number of objective determinants, to include a more holistic focus. Starting to measure health and wellbeing via the lens of the social determinants of health will help to identify where policy-makers and programmes can intervene to begin to more adequately address inequities.